Rapid atmospheric carbon dioxide fixation by nickel(ii) complexes: meridionally coordinated diazepane-based 3N ligands facilitate fixation. Issue 23 (21st May 2021) - Ajaykamal, Tamilarasan; Sharma, Mitu; Islam, Nasreen S.; Palaniandavar, Mallayan
Abstract : In basic methanol solution, [Ni(3N)(H2 O)3 ] 2+ 1, where 3N is a meridionally coordinated ligand, absorbs atmospheric CO2 rapidly to produce 3, [Ni2 (3N)2 (μ-CO3 )(H2 O)2 ](ClO4 )2 . 3 catalyses the conversion of styrene epoxide into cyclic carbonate. Abstract : Octahedral complexes of the type [Ni(L)(H2 O)3 ](ClO4 )2 (1 and 2 ), where L is the tridentate 3N ligand 4-methyl-1-(pyrid-2-ylmethyl)-1, 4-diazacycloheptane (L1, 1 ), or 4-methyl-1-( N -methylimidazolyl)-1, 4-diazacycloheptane (L2, 2 ), have been isolated and characterized using elemental analysis, ESI-MS and electronic absorption spectroscopy. The DFT optimized structures of 1 and 2 reveal that the tridentate 3N ligands are coordinated meridionally constituting a distorted octahedral coordination geometry around nickel(ii ). In methanol solution, the complexes, upon treatment with triethylamine, generate the reactive red colored low-spin square planar Ni–OH intermediate [Ni(L1/L2)(OH)] + (1a and 2a ), as characterized by ESI-MS and electronic absorption spectroscopy, and energy minimized structures. The latter when exposed to the atmosphere rapidly absorbs atmospheric CO2 to produce the carbonate bridged dinickel(ii ) complexes [Ni2 (L1/L2)2 (μ-CO3 )(H2 O)2 ](ClO4 )2 (3 and 4 ), as characterized by elemental analysis and the IR spectral feature (∼1608 cm −1 ) characteristic of bridging carbonate. The single crystal X-ray structure of 3 reveals the presence of a dinickel(ii ) core bridged by a carbonate anion in a symmetric mode. Both the Ni(ii ) centers are identical to each other with each Ni(ii ) possessing a distorted octahedral coordination geometry constituted by a meridionally coordinated 3N ligand, a carbonate ion and a water molecule. The decay kinetics of the red intermediates generated by 1 ( k obs, 7.7 ± 0.1 × 10 −5 s −1 ) and 2 ( k obs, 5.8 ± 0.3 × 10 −4 s −1 ) in basic methanol solution with atmospheric CO2 has been determined by absorption spectroscopy. DFT studies illustrate that meridional coordination of the 3N ligand and the electron-releasing imidazole ring as in 2 facilitate fixation of CO2 . The carbonate complex 3 efficiently catalyzes the conversion of styrene oxide into cyclic carbonate by absorbing atmospheric and pure CO2 with excellent selectivity.